A.P. CHEKHOV’S COMMUNICATION STRATEGIES IN ASYA VOLOSHINA’S PLAY “THE LADY WITH THE DOG” - Larisa G. Tyutelova (Izvestiâ Ûžnogo Federalʹnogo Universiteta: Filologičeskie Nauki, 2022)
The work is devoted to the study of Chekhov’s communicative strategies and the possibility of their use by modern authors when staging Chekhov’s prose. It is proved that modern plays based on Chekhov’s short stories reveal the peculiarities of the presentation of events in the prose of the classic of Russian literature. These features allowed Chekhov to express the complexities of subjective relations at the turn of the XIX and XX centuries, when for the first time the communicative crisis characterizing the relationship of the Self and the Other manifested itself.